EKSISTENSI TOKOH UTAMA DALAM NOVEL YAKUZA NA TSUKI KARYA SHOKO TENDO - Herlina Putri, Kadek Ayu (Humanis; Volume 3. No. 1. April 2013, 2013)
The title of this study is “Eksistensi Tokoh Utama dalam Novel Yakuza Na Tsuki Karya Shoko Tendo”.  The data source  of  this  study  was taken from Japanese  novel entitled  Yakuza Na Tsuki. The study used descriptive analysis and formal methods. The theory used ini analyzing the main character of the novel was taken from the theory of existence proposed by Abidin (2007). The analyzing of existence were classified into two   points of ningen kankei ( ????): miuchi ( ??) and nakama ( ??). The result of analysis showed that the existence of the main character were done in the relation of the people around (ningen kankei).
Keywords: Existence, The Main Character, Yakuza